THE IMPACT OF PARENTING PATTERNS ON THE MULTIPLE INTELLIGENCE OF ELEMENTARY SCHOOL STUDENTS - Izzah Lintang Masyitoh; Agung Setyawan; Mohammad Usman; Moh Rahbini (maktab: Jurnal Pendidikan dan Teknologi, 2022)
Multiple intelligence is an intelligence possessed by a person in a complex way so that the person can be said to be good at everything. Intelligence is not just Intelligence Quotient (IQ), therefore a high IQ without good effort is not good intelligence. Children should be judged on what they do not what they cannot do. This study aims to analyze the effect of parenting style on the multiple intelligences of elementary school students. This type of research is literature study or library research. For data collection that has been used, namely using library research or library research, namely to obtain data, you can utilize library sources. Take notes or read and manage books as research material. The results of the study show that each parent has different ways and styles of parenting, in educating and caring for children so that they can grow self-confidence, independence, and develop their talents and potential, which is the most important thing for parents to their children. So that children are able to deal with unexpected situations and conditions in the future